2010
DOI: 10.1017/s1355617710000524
|View full text |Cite
|
Sign up to set email alerts
|

Community attitudes toward individuals with traumatic brain injury

Abstract: Explicit and implicit attitudes toward people who have sustained traumatic brain injury (TBI) were investigated to determine if negative attitudes exist and if the terminology used (brain vs. head injury) exacerbated predicted negativity. Participants (n = 103) rated Tony (brain/head injury) and Peter (limb-injury) on 10 characteristics using a 7-point scale. Familiarity with brain injury was also measured. Implicit Association Tests (IAT) assessed potential negative bias. Tony (M = 36.84) was judged more nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 20 publications
(32 reference statements)
2
23
1
Order By: Relevance
“…33,34 The current findings support this and a need for continued efforts to promote awareness of ABI in the community. Previous research has described ABI as a "hidden disability," noting the challenges associated with a lack of awareness and understanding of the nature of brain injury among people in the wider community.…”
Section: Discussionsupporting
confidence: 75%
“…33,34 The current findings support this and a need for continued efforts to promote awareness of ABI in the community. Previous research has described ABI as a "hidden disability," noting the challenges associated with a lack of awareness and understanding of the nature of brain injury among people in the wider community.…”
Section: Discussionsupporting
confidence: 75%
“…It has previously been found that those unfamiliar with traumatic brain injury were more likely to hold negative biases [37]. Furthermore, previous research has also identified that even professionals familiar with ABI can possess prejudicial attitudes, particularly if there is the sense that the patient may be to blame for their injury [38].…”
Section: Limitationsmentioning
confidence: 99%
“…Parents nominated fewer days before they felt their child would be ready to return-to-play when the terminology concussion was used compared to other diagnostic termin- The adult injury studies from Table I show that terminology can influence the stigmatization by members of the public of adults who have sustained an mTBI [12,13]. That is, when a hypothetical person with a history of mTBI is labelled as brain injured as opposed to head injured, the public is more likely to associate that person with more negative attributes [12,13].…”
Section: Referencementioning
confidence: 99%
“…That is, when a hypothetical person with a history of mTBI is labelled as brain injured as opposed to head injured, the public is more likely to associate that person with more negative attributes [12,13]. Similarly, when the public rated perceptions of a motor vehicle accident (MVA) related injury that was diagnosed as an mTBI as opposed to a diagnosis of minor head injury (MHI) or concussion, they typically perceive worse consequences [14], including symptoms typically associated with other conditions such as post-traumatic stress disorder [14], unless the diagnosis is conveyed with other information (i.e.…”
Section: Referencementioning
confidence: 99%